Associations between dietary intake of total protein and sources of protein (plant vs. animal) and risk of all‐cause and cause‐specific mortality in older Australian men: The Concord Health and Ageing in Men Project. Issue 5 (21st November 2021) - Das, Arpita; Cumming, Robert; Naganathan, Vasikaran; Blyth, Fiona; Couteur, David G. Le; Handelsman, David J.; Waite, Louise M.; Ribeiro, Rosilene V. R.; Simpson, Stephen J.; Hirani, Vasant
Abstract: Background: The association between dietary protein intake and the risk of mortality is still controversial. The present study aimed to examine the associations between dietary total, animal and plant protein intake and all‐cause and cause‐specific mortality. Methods: Community‐dwelling men aged ≥ 70 years were recruited from local government areas surrounding Concord Hospital in Sydney, New South Wales for the Concord Health and Ageing in Men Project (CHAMP). The research dietitian administered a standardised validated diet history questionnaire to capture baseline dietary intake. In total, 794 men participated in a detailed diet history interview at the third wave. Adequacy of protein intake was assessed by comparing participant intake with the Nutrient Reference Values. Total protein intake was categorised into quintiles. Sources of protein were also captured. Mortality was ascertained through the New South Wales death registry. Cox proportional hazard models were used to assess the association between dietary total, animal and plant protein intake and risk of mortality. Results: The mean age of the CHAMP men was 81 years. In total, 162 men died during a median follow‐up of 3.7 years. Of these, 54 (33.3%) and 49 (30.2%) men died due to cancer and cardiovascular disease, respectively. There were U‐shaped associations between protein intake and all‐cause and cancer mortality. In multiple adjusted analysis, the second (hazard ratio [HR] = 0.38; 95% confidence interval [CI] = 0.18–0.82) and third (HR = 0.36; 95% CI = 0.16–0.82) quintiles of protein intakes were significantly associated with reduced risk of all‐cause and only second quintile (HR = 0.47; 95% CI = 0.10–0.93) of protein intake was significantly associated with cancer mortality. Each serve increase in animal protein was significantly associated with 12% (HR = 1.12; 95% CI = 1.00–1.26) and 23% (HR = 1.23; 95% CI = 1.02–1.49) increased risk of all‐cause mortality and cancer mortality respectively. Conversely, each serve increase in plant protein intake was significantly associated with 25% (HR = 0.75; 95% CI 0.61–0.92) and 28% (HR = 0.72; 95% CI = 0.53–0.97) reduced risk of all‐cause and cancer mortality, respectively. No such associations were observed for cardiovascular disease mortality. Conclusions: Both second and third quintiles of total protein intake were associated with reduced all‐cause and cancer mortality. Plant protein was inversely associated with all‐cause and cancer mortality, whereas animal protein intake was positively associated with mortality. Abstract : Key points: Our findings suggest a U‐shaped association between life expectancy and total protein intake, in which lifespan is greatest among people with 93–113 g day –1 total protein intake, a level that might be considered moderate in Australia but high in other countries. Both second and third quintiles of total protein intake (range between 79.23 and 107.19 g day –1 ) were associated with reduced risk of all‐cause and cancer mortality. Higher consumption of animal‐derived proteins was associated with greater mortality risk, whereas this association was reversed when protein consumption was replaced with plant‐derived protein.